The pro-BNP Serum Level and Echocardiographic Tissue Doppler Abnormalities in Patients with Beta Thalassemia Major - Garadah, Taysir S. (Libertas Academica, 2010)
BACKGROUND: Doppler echocardiographic studies of the left ventricle (LV) function in patients with β-Thalassemia Major (β-TM) had shown different patterns of systolic and diastolic dysfunctions associated with abnormal serum brain natriuretic peptide (BNP). AIM: This cross-sectional study was designed to study the LV systolic and diastolic functions and correlate that with serum level of N-terminal pro brain natriuretic hormone (NT- pro BNP) in patients with β-TM using Pulsed Doppler (PD) and Tissue Doppler (TD) echocardiography. METHODS: The study was conducted on patients with β-TM (n = 38, age 15.7 ± 8.9 years) and compared with an age-matched controls (n = 38, age 15.9 ± 8.9 years). In all participants, PD and TD echocardiography were performed and blood samples were withdrawn for measuring the serum level of NT-pro BNP, ferritin, and alanine transaminase. RESULTS: Patients with β-TM compared with controls, have thicker LV septal wall index (0.65 ± 0.26 vs. 0.44 ± 0.21 cm, P < 0.001), posterior wall index (0.65 ± 0.23 vs. 0.43 ± 0.21 cm, P < 0.01), and larger LVEDD index (4.35 ± 0.69 vs.3.88 ± 0.153 mm, P < 0.001). In addition, β-TM patients have higher transmitral E wave velocity (E) (70.818 ± 10.139 vs. 57.532 ± 10.139, p = 0.027) and E/A ratio (1.54 ± 0.17 vs. 1.23 ± 0.19, P < 0.01) and shorter deceleration time (DT) (160.13 ± 13.3 vs. 170.50 ± 19.20 m sec, P < 0.01). Furthermore, the ratio of transmitral E wave velocity to the tissue Doppler E wave at the basal septal mitral annulus (E/Em(−)) was significantly higher in β-TM group (19.6 ± 2.81 vs. 13.868 ± 1.41, P < 0.05). The tissue doppler systolic wave (Sm) velocity and the early diastolic wave (Em) were significantly lower in β-TM group compared to controls (Sm: 4.82 ± 1.2 vs. 6.22 ± 2.1 mm/sec, P < 0.05; Em: 3.51 ± 2.7 vs. 4.12 ± 2.5 mm/sec P < 0.05, respectively). The tricuspid valve velocity was significantly higher in β-TM patients compared with controls (2.993 ± 0.569 vs. 1.93 ± 0.471 m/sec, respectively, P < 0.01). The mean serum NT pro-BNP in β-TM was significantly higher compared with controls (37.6 ± 14.73 vs. 5.5 ± 5.4pg/ml, P < 0.05). The left ventricle ejection fraction (EF%) and fractional shortening (FS%) were not significantly different between both groups. CONCLUSION: We conclude that patients with β-TM had a significantly higher serum level of NT-pro BNP that is positively correlated with the E/Em ratio on tissue Doppler. Furthermore, we confirm our previous findings that patients with β-TM exhibit LV diastolic pattern on echocardiogram suggestive of restrictive type with well preserved left ventricle systolic function.